2012
DOI: 10.1177/2165143412468147
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Nonacademic Behaviors Associated With Post-School Employment and Education

Abstract: We conducted an analysis of the secondary transition qualitative and quantitative research literature to build comprehensive constructs and lists of student nonacademic behaviors associated with post–high school employment and education. From a pool of 83 initial quantitative and qualitative studies, 35 met the inclusion criteria, and the analysis of these yielded 10 constructs of student nonacademic behaviors associated with post-school education and employment for high school students with mild to moderate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 34 publications
0
36
1
Order By: Relevance
“…Table 1 contains a description of webbased transition resources. evidence-based practices that support post-school goals (e.g., Mazzotti et al, 2016;McConnell et al, 2013;Test et al, 2009). Rowe et al (2015) translated research-to-practice by defining predictors of positive post-school outcomes and provided examples of how these predictors can be addressed by schools.…”
Section: Be a Resource Expertmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 contains a description of webbased transition resources. evidence-based practices that support post-school goals (e.g., Mazzotti et al, 2016;McConnell et al, 2013;Test et al, 2009). Rowe et al (2015) translated research-to-practice by defining predictors of positive post-school outcomes and provided examples of how these predictors can be addressed by schools.…”
Section: Be a Resource Expertmentioning
confidence: 99%
“…Teams should review relevant research to identify specific evidencebased practices that support post-school goals (e.g., Mazzotti et al, 2016;McConnell et al, 2013;Rowe et al, 2015;Test et al, 2009).…”
Section: Steps To Develop Transition Coordinator Positionmentioning
confidence: 99%
“…To improve the efficacy of transition planning, McConnell et al (2013) identified from the research literature non-academic behaviors associated with postsecondary education and employment of former students with disabilities. Martin et al (2015a) used these constructs to develop a new 2015b, through an iterative process, developed the items, rating scales, and instructions for the Professional, Student, and Family TAGG versions.…”
Section: Instrumentationmentioning
confidence: 99%
“…In all cases, the focus person should be as involved as possible in coming up with, putting into place, and evaluating solutions. This is in and of itself a major aspect of self-determination (McConnell et al, 2013).…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…Gathering all of this "discovery" information is only as useful as the extent to which many ideas are generated -for taking action. In turn, action requires goal-setting (Holland, 1997;McConnell et al, 2013;. Life coach and counselor Nancy Schlossberg (1994) frames it this way: effective planning requires that people "take stock of" their situations, themselves, their supports and their strategies.…”
Section: Goal-setting/planningmentioning
confidence: 99%